Respuesta :

Can't make out your first term, so I will assume that it is -4.

The common ratio of this geom. seq. is 6.

Thus, a(n) = -4(6)^(n-1)

Check:  if n = 3, do we get -144 as the 3rd term?

a(3) = -4(6)^(3-1) = -4(6)^2 = -4(36) = -144.   YES.

Answer: The formula that can be used to describe the sequence is given by [tex]a_{n+1}=-6\times a_n[/tex]

Step-by-step explanation:

Since we have given that

-, −4, −24, −144,...

Here, we can see that

-4 × 6 = -24

-24 × 6 = -144

So, [tex]a_1=-4[/tex]

So, the recursive formula will be

[tex]a_{n+1}=-6\times a_n[/tex]

Hence, the formula that can be used to describe the sequence is given by [tex]a_{n+1}=-6\times a_n[/tex]